MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN SISWA KELAS I MELALUI PRODUKSI KETERAMPILAN TANGAN (ANYAMAN, ORIGAMI, DAN MEREMAS) DI SEKOLAH DASAR - Eliyanti; Lyesmaya, Dyah; Uswatun, Din Azwar (PREMIERE : Journal of Islamic Elementary Education, 2023)
This research is based on the low writing ability of first grade students at SDN 3 Ciracap. The purpose of this study was to describe the planning, implementation, and results of hand skills production activities (plaiting, origami, and squeezing) to improve initial writing skills in research subjects. The researcher used the classroom action research method first grade students at SDN 3 Ciracap with a total of 30 people. The research was conducted from February 2023 to June 2023 at SDN 3 Ciracap, Ciracap District. Data collecting techniques used was: tests, observations, and literature studies, then analyzed using descriptive statistics. The results of the analysis show that before being given action, students' writing skills tend to be low where students cannot write neatly, the letters used are wrong, the spelling is not correct, and students do not write complete sentences. After giving the action (cycle II) the students' initial writing ability was assessed to increase significantly by practicing the production of hand skills (plaiting, origami, and squeezing). Students can write neatly, the letters used are correct, the spelling is correct, and students write complete sentences. The average value of students' initial writing ability in the pre-cycle was 45.53 with a classical completeness percentage of 0% with low criteria. In cycle I the average value obtained was 58.20 with a classical completeness percentage of 3.33% with moderate criteria. Whereas in cycle II the average value obtained was 85.07 with a 100% classical completeness percentage with very high criteria.